Analisis Tingkat Kemiskinan dan Faktor Yang Memengaruhi di Jawa Timur - Nadya Septian Monica; Dwi Susilowati (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This research examines the impact of the open unemployment rate, average years of schooling, and population growth on poverty levels in districts and municipalities across East Java Province during the 2019-2023 period. By employing panel data regression and a quantitative approach, the study identifies key determinants of poverty and visualizes their geospatial distribution. The findings indicate that the open unemployment rate significantly increases poverty, whereas the average years of schooling significantly reduces it. On the other hand, population growth exhibits a positive but statistically insignificant effect. A simultaneous test confirms that the independent variables collectively influence poverty, contributing 99.03% to its variation. The study underscores the importance of improving access to education, creating employment opportunities, and managing population growth as essential strategies for poverty alleviation. These findings are intended to serve as a foundation for strategic and sustainable poverty reduction policies in East Java.